PENERAPAN PENDEKATAN PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN HASIL BELAJAR MATEMATIKA SISWA POKOK BAHASAN PROGRAM LINIER KELAS XIIA SMA DARUS SHOLAH TAHUN AJARAN 2013/2014 - Robbah, Hossiyatur; Sunardi, S; Setiawani, Susi (KadikmA, 2015)
Abstract. In general, mathematics learning at schools is a teacher centered, so the students become less active in teaching-learning process. It also causes the low score of the student learning achievement. Therefore, it needs a development of learning by applying a problem posing approach in program linier topic to improve the student learning achievement of class XII A in SMA Darus Sholah 2013/2014 academic year. The research methods are documentation, observation, test and interview. The data which is analysed are teacherâs activities, studentsâ activities and studentsâ test result. Final result of this research is the increasing of studentsâ activities and learning in class XII A SMA Darus Sholah the improvements of studentsâ activities are indicated by the average score of 71,05% for the first cycle, 85,96% for the second cycle of the action research. While the studentsâ learning increased significantly from 52,63% in tne first cycle to 89,47% in the second cycle of action research. It can be concluded that the Problem Posing approach is effective to improve the student learning achievement of class XII A in SMA Darus Sholah 2013/2014 academic year. Key Words: activities, student learning achievement, problem posing approach, program linier.